Essentials in Hip and Ankle - Suarez-Ahedo, Carlos; Olivos-Meza, Anell; Rijke, Arie M. (IntechOpen, 2020)
Each chapter of this book covers physical examination, imaging, differential diagnoses, and treatment. For each diagnosis, the book sets out the typical presentation, options for non-operative and operative management, and expected outcomes. Each chapter is concise enough to be read easily. Users can read the text from cover to cover to gain a general foundation of knowledge. Practical and user-friendly, Essentials in Hip and Ankle is the ideal, on-the-spot resource for medical students and practitioners seeking fast facts on diagnosis and management. Its format makes it a perfect quick-reference, and its content breadth covers commonly encountered orthopedic problems in practice.